The Implementation of the Simple Multi Attribute Rating Technique Method for Evaluating the Guidance Process for the Final Project of the Applied Software Engineering Technology Students - Idmayanti, Rika; Meidelfi, Dwiny; Rahmayuni, Indri; Sukma, Fanni; Ramadhani, - (International Journal of Advanced Science Computing and Engineering, 2021)
Simple Multi Attribute Rating Technique (SMART) is a method that is able to solve problems with multi criteria. In the evaluation of the final project guidance process students of applied software engineering technology are intended to identify supporting factors as well as obstacles for students in completing the final project. Used several criteria such as liveliness of guidance, guidance response, how to communicate, mastery of materials, problem solving and report writing. The problem in determining the cause of the hampered completion of the final project is the lack of tools that can help in processing the criteria data. The solution is to utilize the SMART method with multi criteria problem solving as a tool in decision making. With the utilization of this method is expected to provide solutions in evaluating the guidance process so that the results can be accepted by all students objectively. With the decision support system model, it is expected to be able to know the problem factor in completing the final project so as to help in the implementation of the final project in the next period.